The COVID-19 vaccine did not affect the basal immune response and menstruation in female athletes - Ishida, Y.; Yamagishi, T.; Mujika, I.; Nakamura, M.; Suzuki, E.; Yamashita, D. (Physiological Reports, 2023)
The COVID-19 pandemic restricted the regular training and competition program of athletes. Vaccines against COVID-19 are known to be beneficial for the disease; however, the unknown side effects of vaccines and postvaccination reactions have made some athletes hesitant to get vaccinated. We investigated the changes in inflammatory responses and menstrual cycles of female athletes before and after vaccination. Twenty female athletes were enrolled in this study. Blood was collected from each subject before the first COVID-19 vaccination and after the first and second vaccinations. Laboratory data, including white blood cell, neutrophil, lymphocyte, and platelet counts, and inflammatory markers, including NLR (neutrophil-to-lymphocyte ratio), PLR (platelet lymphocyte ratio), RPR (red cell distribution width to platelet ratio), SII (systemic immune-inflammation index), and NeuPla (neutrophil-platelet ratio), were analyzed statistically. The menstrual changes before and after vaccination and the side effects were collected by questionnaires. No significant changes in the laboratory data were found after the first and second shots when compared to those at prevaccination: white blood cell, neutrophil, lymphocyte, platelet, NLR, PLR, SII, RPR, and NeuPla (p > 0.05). In addition, there were no significant changes in the menstruation cycle or days of the menstrual period (p > 0.05). All side effects after vaccination were mild and subsided in 2 days. The blood cell counts, inflammatory markers, and menstruation of female athletes were not affected by COVID-19 vaccines.